Parental Attention and Self Control among Student Athletes and Non Athletes: A Metacognitive Perspective - Purnama Yusti Herasakti Hera; Nopem Kusumaningtyas Sumitro; Ahmad Lani (Yayasan Azhar Amanaa Yogyakarta, 2026)
The ability of self-control is a crucial psychological foundation for elementary school children to face academic and social challenges. This qualitative study using a comparative case study design aims to explore how parental attention affects the formation of self-control in two groups of students with different background activities: student athletes and non-athletes at SDN Sumbersari I Beji. Data were collected through in-depth interviews with 10 informants (parents, students, classroom teachers, and physical education teachers), behavioral observation at school, and disciplinary records analysis. The results showed differences in variable interaction mechanisms. In the group of student athletes, structured physical training and a strict competitive climate act as external reinforcement that accelerates the internalization of self-control, so that parental attention is more oriented toward maintaining emotional stability to prevent burnout. Conversely, in the non-athlete group with a more flexible daily pattern, parental attention—especially through two-way communication and active monitoring—plays an absolute role as the primary regulator in restraining digital distractions. These findings emphasize that the effectiveness of parental attention in shaping children's character highly depends on the structure of daily activities followed by children outside the home.